Sudden cardiac death in young athletes; a literature review and special considerations in Asia - Halabchi, F.; Seif-Barghi, T.; Mazaheri, R. (Asian Journal of Sports Medicine, 2011)
Sudden cardiac death (SCD) in a young athlete is rare, but catastrophic. Exercise acts as a risk factor for SCD in people with cardiovascular disease. A diversity of cardiovascular disorders including hypertrophic cardiomyopathy, congenital coronary anomalies, arrhythmogenic right ventricular dysplasia, dilated cardiomyopathy, aortic rupture due to Marfan syndrome, myocarditis, valvular disease and electrical disorders (Wolff-Parkinson-White syndrome, long QT syndrome, Brugada syndrome), as well as commotio cordis represent the common causes of SCD in young athletes.